A socially constructed framework for culturally congruent nursing curriculum transformation in Lesotho: A Multi-Methods approach - Nthabiseng Ann Molise; Yvonne Botma; Deirdre Van Jaarsveldt (Elsevier, 2024)
Background: Implementing a transformative nursing curriculum is strategic for a country's population health outcomes. However, transforming a nursing curriculum is challenging due to the lack of investigation into cultural influences impacting such transformation.Therefore, in order to implement a transformative nursing curriculum, educators need support to explore what a culturally congruent framework would look like. Purpose: To socially construct a framework for culturally congruent nursing curriculum transformation in Lesotho. Methodological approach: This study used a descriptive, qualitative, multiple-method research approach. The transformative learning theory was the theoretical context within the social constructivism research paradigm. The Mmogo-MethodTMand the KAWA technique were methods used for data collection during the study's two empirical phases. The Mmogo-MethodTM was used to describe cultural influences on curriculum implementation, while the KAWA technique was used to describe the congruency between culture and transformative curriculum implementation. Out of a population of 11, a convenience sample of seven midwifery educators was used for the Mmogo-MethodTM and a criterion purposive samplingselection of 14 nursing educatorsfrom a population of 64 for the KAWA technique. Additionally, a narrative literature review was systematically performed to establisha relationship between culture and transformative curriculum implementation. Findings and interpretations: Empirical findings from the Mmogo-MethodTM, KAWA technique, and the narrative literature review confirmed that culture might well influence the implementation of a transformative nursing curriculum. The findings were used to draft a framework validated by nursing educators. The three emergent framework concepts were: transformative learning; educators; and students. These three concepts were inter-related throughout the learning process.